Time/Space Polyphony in David Mitchell’s “Cloud Atlas” and Its Eponymous Film Adaptation - Matiychak, Aliona; Nikoriak, Natalia (Yuriy Fedkovych Chernivtsi National University, 2025)
The study examines the spatiotemporal narrative polyphony of David Mitchell’s metanovel “Cloud Atlas” and its cinematic interpretation in the eponymous film adaptation. It focuses on the specificity of the novel’s multi-layered narrative, constructed according to a palindromic principle in which six stories form a complex web of cross-references and causal relationships. In this way, the text becomes an experiment in genre and narrative design with “echo effect,” whereby each story reflects the preceding one and anticipates the next. The analysis traces how spatial and temporal modalities ‒ from the historical past to a post-apocalyptic future ‒ are interwoven into a unified philosophical network in which every choice shapes what is yet to come. Emphasis is placed on the role of reincarnation as a pervasive symbolic mechanism: the motif of the “comet-shaped birthmark” signifies the continuity of a single soul across its various incarnations, while the central ethical imperative of the narrative emerges as the responsibility inherent in individual choice. The novel’s musical metasymbol ‒ the Cloud Atlas Sextet ‒ functions as an artistic matrix mirroring the novel’s fragmentary yet structurally harmonious architectonics. Intermediality is treated as a foundational structural principle of the novel, with each of the narratives rendered through a distinct mode of textual representation ‒ journal, epistolary correspondence, manuscript, screenplay, holographic recording, or legend ‒ thus generating a multi-layered effect of “post-memory” and facilitating fluid transitions between historical epochs. The study also examines the linguistic stylisation that captures the ambiance of each period. In a comparative framework, the study traces the unfolding of the same ideas within the cinematic dimension. Filmmakers Tykwer and the Wachowskis employ the principle of parallel montage, which enables the simultaneous dynamism of the six narrative strands. The system of visual rhymes reinforces the notion of reincarnational affinities among the characters. The phenomenon of actor transfigurations, whereby a single performer embodies multiple roles across different eras, renders visible the metaphor of the soul’s continuity and the recurrence of ethical impulses. The discussion highlights that the film not merely adapts but re-envisions the novel’s architectonic design, constructing its cinematic counterpart as a kind of “pointillist mosaic,” in which the composition is generated through alternating segments unified by a musical leitmotif and sustained by visual parallels. It is also stressed that music assumes the status of a fully autonomous character within the adaptation, performing a crucial suggestive function by shaping the viewer’s “emotional amplitude” in the reception of events and characters.
Keywords: David Mitchell; “Cloud Atlas”; metanovel; film adaptation; palindrome; spatiotemporal polyphony; multi-layered narrative; post-memory